GPU Algorithm for Enumerating PL Spheres of Picard Number 4: Application to Toric Topology - Choi, Suyoung; Jang, Hyeontae; Vallée, Mathieu (Leibniz International Proceedings in Informatics, LIPIcs, 2024)
The fundamental theorem for toric geometry states a toric manifold is encoded by a complete non-singular fan, whose combinatorial structure is the one of a PL sphere together with the set of generators of its rays. The wedge operation on a PL sphere increases its dimension without changing its Picard number. The seeds are the PL spheres that are not wedges. A PL sphere is toric colorable if it comes from a complete rational fan. A result of Choi and Park tells us that the set of toric seeds with a fixed Picard number p is finite. In fact, a toric PL sphere needs its facets to be bases of some binary matroids of corank p with neither coloops, nor cocircuits of size 2. We present and use a GPU-friendly and computationally efficient algorithm to enumerate this set of seeds, up to simplicial isomorphism. Explicitly, it allows us to obtain this set of seeds for Picard number 4 which is of main importance in toric topology for the characterization of toric manifolds with small Picard number. This follows the work of Kleinschmidt (1988) and Batyrev (1991) who fully classified toric manifolds with Picard number ≤ 3.
Keywords: Binary matroids; Characteristic map; GPU algorithms; GPU-programming; Parallel com- puting; Picard number; PL sphere; Simplicial spheres; Toric manifold; Weak pseudo-manifold; binary matroid; characteristic map; GPU programming; parallel computing; Picard number; PL sphere; simplicial sphere; toric manifold; weak pseudo-manifold